Respostas
respondido por:
0
aqui temos uma composta de função, logo é uma função que substitui o x em outra função:
g(x) = 2x + 1
f(x) = x - 3
g(f(x)) = 2 (x - 3) + 1
g(f(x)) = 2x - 6 + 1
g(f(x)) = 2x - 5
g(x) = 2x + 1
f(x) = x - 3
g(f(x)) = 2 (x - 3) + 1
g(f(x)) = 2x - 6 + 1
g(f(x)) = 2x - 5
respondido por:
0
Resposta:
g(x) = 2.x +1 e f(x)= X -3
g(f(x))=
Explicação passo-a-passo:
g(f(x))= 2 (x-3)+1
g(f(x))=2x-6+1
g(f(x))=2x-5
Perguntas similares
3 anos atrás
3 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás